Pre-Shift Smoking Cessation Training for Early Medical School Students in a New Orleans Substance Use Rehabilitation Center - Tsakiris, Eli; Payne, Kathryn; Staav, Johnathan; Yazbeck, Andrea; Rao, Neha; Vodovoz, Samuel; Donthi, Sriti; Sala, Matthew; Power, Caroline; Ratakona, Sanjana; Pope, Helen (Journal of Student-Run Clinics, 2025)
Background: Large-scale studies have reinforced our understanding of smoking as the likely single most important modifiable risk factor affecting health and longevity. Although medical students receive instruction on how to navigate lifestyle change conversations with patients, specific education on how to perform smoking cessation counseling is minimal and comes later in their didactic years. Rates of smoking within the general United States population have declined, but smoking rates remain high in patients with comorbid substance use disorder. Our analysis evaluates the implementation of a 15-minute pre-shift training on smoking cessation counseling, for volunteers at a student-run clinic set in a substance use rehabilitation center. Methods: The smoking cessation volunteer training takes place in the 15 minutes preceding the volunteer’s shift. The on-shift leader first facilitates an open discussion on smoking cessation between all volunteers to gauge their level of knowledge and experience with the content. Areas of focus are divided into medical cessation aids and conversational techniques. The leader then guides all volunteers through a review of the information, ensuring they answer all volunteer questions. First-year students are then encouraged to complete an electronic survey sent out via email following their volunteer shift. Results: Between 8/16/2023-10/25/2024, 54 responses were received from approximately 150 eligible volunteers, a response rate of 36%. Of surveyed volunteers, 76% reported having a discussion on smoking cessation during their shift. In response to whether the pre-shift training helped their ability to address this topic with patients, 67% answered “definitely yes”, 24% answered “somewhat yes”, and no students reported the session as unhelpful. Conclusion: Most medical student volunteers at New Orleans Bridge House engage in smoking cessation discussions with a patient during each shift. Nearly every surveyed volunteer believed they benefited from brief pre-shift training and the majority learned about at least one new cessation aid.